Interdisciplinary interaction design a visual guide to basic theories, models and ideas for thinking and designing for interactive web design and digital device experiences - Pannafino,James (Assiduous Publishing, 2012)
"Interaction design has many dimensions to it. It addresses how people deal with words, read images, explore physical space, think about time and motion, and how actions and responses affect human behavior. Various disciplines make up interaction design, such as industrial design, cognitive psychology, user interface design and many other." -- Publisher